2011
DOI: 10.1348/014466510x500837
|View full text |Cite
|
Sign up to set email alerts
|

Clinical correlates of olfactory hallucinations in schizophrenia

Abstract: OBJECTIVES. Olfactory hallucinations (OHs) are underrepresented in conventional clinical instruments, infrequently researched, and poorly understood. To advance understanding of OHs, we examined their past-month prevalence and co-occurring symptoms in two datasets. DESIGN. One dataset comprised categorical codes and was examined using homogeneity analysis and logistic regression; the other dataset comprised numeric ratings and was examined using principal components analyses and linear regression. METHOD. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 66 publications
(95 reference statements)
1
26
0
Order By: Relevance
“…This suggests olfactory hallucinations are largely a phenomenon that occurs in schizophrenia patients, and to a lesser degree in schizoaffective and bipolar patients. Similar to our findings, olfactory hallucinations were present in 13% of schizophrenia patients in the World Health Organization 10 County dataset, consisting of approximately 1000 patients (Langdon et al, 2011). Other studies have found rates of olfactory hallucinations ranging from 7% to 35% of their schizophreniaspectrum samples (reviewed in Langdon et al, 2011).…”
Section: Longitudinal Trajectory Of Auditory and Visual Hallucinationssupporting
confidence: 89%
“…This suggests olfactory hallucinations are largely a phenomenon that occurs in schizophrenia patients, and to a lesser degree in schizoaffective and bipolar patients. Similar to our findings, olfactory hallucinations were present in 13% of schizophrenia patients in the World Health Organization 10 County dataset, consisting of approximately 1000 patients (Langdon et al, 2011). Other studies have found rates of olfactory hallucinations ranging from 7% to 35% of their schizophreniaspectrum samples (reviewed in Langdon et al, 2011).…”
Section: Longitudinal Trajectory Of Auditory and Visual Hallucinationssupporting
confidence: 89%
“…In the visual modality, complex perceptual abnormalities typically take the shape of a person, a face, an animal, a landscape or a scene, while simple perceptual abnormalities may take the form of flashes, shapes, geometric patterns, or shadows (Blom, 2010; Ffytche and Wible, 2014). Despite the documentation of the diversity of hallucinatory experiences, current research on hallucinations in psychiatric populations has mainly focused on auditory verbal hallucinations while hallucinations in other modalities or subtypes of hallucinations are less well understood (Langdon et al, 2011; Waters et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…The selected ROIs, shown in Figure 7, were all mid-line frontal regions, and mostly connected in the MRF prior. The frontal superior orbital, olfactory and rectus regions have all reported schizophrenia deficits, see Nakamura et al (2008), Diaz et al (2011) and Langdon et al (2011), among many others. The left frontal region included the Brodmann area 10, identified by the cross-hair in Figure 7, which is often implicated in schizophrenia (Vogeley et al, 2003; Camchong et al, 2008; Schneiderman et al, 2011).…”
Section: Applicationsmentioning
confidence: 94%